The Effect Of Flexible Work Space And Work Discipline On Work Productivity (Study On Employees In The City Of Surakarta) - Ali , Husin; Kusdiyanto , Kusdiyanto (Jurnal Economic Resource, 2024)
In this digital era, the world of work is undergoing a significant transformation. The emergence of information and communication technology (ICT) opens up new opportunities for companies to implement more flexible work models. One of the increasingly popular flexible work models is flexible work space (FWS). FWS allows employees to work from anywhere and anytime, not limited to traditional office space. As technology advances, it is necessary to adapt to using this technology. In new routines and habits in their lives, employees become more skilled in using digital work tools. It must be understood that the digital work environment is flexible and adaptable, allowing companies to adapt and change various work practices without requiring technological changes. (Richter & Riemer, 2013) in the journal (Driyantini et al., 2020). This study uses a quantitative approach with a survey method through a questionnaire distributed online to respondents who meet certain criteria . The results of the study indicate that flexible work space and work discipline have a positive and significant influence on employee work productivity.